Conceptual draft of a three-stage system for protection of localities of rare and threatened plants on the example of the orchid family (Orchidaceae) in Poland - Bernacki, Leszek (Biodiversity: Research and Conservation, 2006)
The present state of safeguarding of localities of plants from the orchid family in Poland within the framework of official forms of nature protection is highly random and thus unsatisfactory. This statement is true both with regard to the percentage of localities which are placed under protection and to the distribution pattern of protection sites which is inadequately correlated with the pattern of occurrence of individual species (or subspecies) in the respective regions of the country. In the face of this situation, an attempt was made to prepare the concept of a universal system which would enable a simple, transparent and objective selection procedure for the most valuable localities of rare or threatened species. The presented project relies on two simple and basic assumptions. The first one is a three-stage design of the system. Natural assets and scientific value serve as criteria for selection and classification of the most valuable localities at one of three levels: the highest national level (red points), the medium-value macroregional level (yellow points) and local level (green points). The second assumption states that for each species (subspecies), a maximum number of 10 localities (points) can be selected in each territorial unit for its respective level. Final result of analysis, as individual maps and plans of protection for each species (subspecies), should serve the realisation of the paramount goal which is the rational management of biological resources. The presented system should also make it easier to select localities which require legal protection as well as serve as a reliable and objective tool for choosing sites for monitoring.